Risk factors associated with positional plagiocephaly in healthy Iranian infants: a case-control study - Soltani, Babak; Talebian Ardestani, Motahare; Boroumand, Homa; Ostadmohammadi, Vahidreza; Kashani Zade, Mansour; Loghman, Amirhossein; Talebian Ardestani, Ahmad (Iranian Journal of Child Neurology, 2022)
Abstract Objectives Deformation of the skull by external forces in the absence of synostosis has been defined as positional plagiocephaly. The aim of this investigation was to determine the risk factors of positional plagiocephaly (PP) in healthy Iranian infants. Materials & Methods This case-control study was performed on 300 healthy Iranian infants aged 8-12 weeks who referred to pediatric neurology clinic at Shahid Beheshti Hospital of Kashan. Plagiocephaly evaluations were done by using Argenta’s scale. Results Based on multivariate logistic regression analysis, there was significant association between PP and male gender (OR=2.26; P=0.002), head circumference (OR=1.22; P=0.006), multiple pregnancy (OR=2.55; P=0.03), abnormal presentation in uterine (OR=2.18; P=0.02), primiparity (OR=2.43; P=0.003), and supine sleep position (OR=2.97; P<0.001). But type of delivery, firmness of headrest, oligohydramnios, and prolonged labor were not correlated with PP. Conclusions The current investigation supports the idea that head circumference, male gender, primiparity, multiple pregnancy, supine sleep position, and abnormal presentation in uterine are correlated with a greater incidence of PP. Further investigations should be undertaken to fully understand PP and its related risk factors.